Optical and Electrical Properties of μ-Slice InGaN/GaN Light Emitting Diodes Shaped by Focused Ion Beam Process - Hsu, Che-Kang; Sheu, Jinn-Kong; Wang, Jia-Kuen; Lee, Ming-Lun; Chang, Kuo-Hua; Tu, Shang-Ju; Lai, Wei-Chih (Applied physics express, 2011)
In this study, slice-type GaN-based light-emitting diodes (μ-slice LEDs) scaled down to a few micrometers using focused ion beam (FIB) process were demonstrated. Electroluminescence peak wavelengths ($λ_{\text{p}}$) of the single μ-slice LEDs were nearly independent of driving current density due to the fact that the effects of joule heating and band filling on the shift of $λ_{\text{p}}$ compete with each other. The smaller full width of half maximum of electroluminescence peaks observed from the μ-slice LEDs could result from the effect of strain release after the FIB process and thermal annealing during the FIB process on sliced structures.